2018
DOI: 10.1002/eji.201747052
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral infections and atopic development: From possible mechanisms to advances in treatment

Abstract: Atopic sensitization and allergic diseases are increasing in modernized countries. These diseases affect millions of individuals, but the mechanisms behind their development are not fully understood. One hypothesis relates to early life respiratory viral infections driving the development of atopic disease including asthma. This review presents the current state of the field, focusing on epidemiologic data supporting a role for early life respiratory viruses in the development of specific IgE, both against aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
1
24
0
5
Order By: Relevance
“…These data are consistent with the notion that early‐life RV infections induce a nonallergic asthma phenotype . It has also been suggested that early‐life RV infections could drive the development of atopic sensitization and subsequent allergic airways disease …”
Section: Discussionsupporting
confidence: 89%
“…These data are consistent with the notion that early‐life RV infections induce a nonallergic asthma phenotype . It has also been suggested that early‐life RV infections could drive the development of atopic sensitization and subsequent allergic airways disease …”
Section: Discussionsupporting
confidence: 89%
“…While essentially all children become infected with Respiratory Syncytial Virus (RSV) in the first two years of life only a small percentage develop severe bronchiolitis and require hospitalization. 35,36 These children tend to be infected in the first 2–6 months of life and have been shown to have a markedly elevated risk for developing asthma (and allergic disease). 35,36 Other studies have shown a similar risk with Metapneumovirus (MPV) and Rhinovirus (RV).…”
Section: Origins Of Pediatric Asthmamentioning
confidence: 99%
“…There is robust evidence concerning the synergistic effect of viral lower respiratory tract infections (LRTI) and IgE sensitization on asthma development, particularly in children predisposed to atopy (72) and asthma exacerbation (73). Increased risks of asthma inception in atopic predisposed children include: the type of virus (more than 10-fold increased risk for asthma development with rhinovirus compared to 5-fold with respiratory syncytial virus); the severity of viral LRTI; and the age during viral LRTI (74). The risk of hospital admission due to asthma exacerbation is increased by the interaction among respiratory viral infections in combination with atopic sensitization and exposure to allergens (75).…”
Section: Role Of Viruses Smoking and Pollutantsmentioning
confidence: 99%